Ultrasonic and electroplating approach for washcoat of γ-alumina and nickel oxide (nio) catalyst on fecral substrate for catalytic converter - Feriyanto, Dafit (2018)
One of the technological advances was concentrated on the removal of pollutants from exhaust system by Three-Way Catalytic Converter (CATCO). Metallic material potential to replace the ceramic material, therefore FeCrAl substrate used as metallic material and γ-Al2O3 as washcoat material and NiO catalyst. This study propose ultrasonic and electroplating approach as coating technique which not fully explored. Several problems in developing CATCO such as washcoat layer is spalling since the loose adhesion and unstable oxide growth in long term oxidation. Therefore, the main objective of this study are to embed γ-Al2O3 into substrate, to improve thermal stability as well as to improve conversion efficiency of exhaust gas emission. The methods performed in this study by ultrasonic bath (UB) using ethanol solution with frequency of 35 kHz and holding time of 1, 1.5, 2, 2.5 and 3 h respectively, electroplating technique (EL), ultrasonic bath during electroplating (UBdEL) and combination of UB and EL which is called by UB+EL technique that conducted by sulphamate type solution, current density of 1.28 A and holding time of 15, 30, 45, 60 and 75 minutes. The results shows that γ-Al2O3 has been embedded into FeCrAl substrate which develop several compounds such as FeCrAl, FeO, γ-Al2O3, FeCr2O3, NiO, NiAlO4, NiCr2O4 and NaO2. Appropriate coating thickness of coated FeCrAl was observed in UB+EL samples of 9.1 to 12 μm. The thermal analysis shows the smallest mass change located at UB+EL 30 minutes sample for 2.85 mg. Therefore, UB+EL 30 min was selected to be a method for FeCrAl CATCO development. Coated FeCrAl CATCO more effective to reduce fuel consumption up to 1.693 L/h and increase torque of 95 Nm, reduce NOx up to 91.66% and HC emission up to 81.4% as well as reduce exhaust gas temperature up to 20.58% as compared to conventional ceramic and metallic CATCO. Therefore, an appropriate techniques and parameter is UB+EL 30 min used for coating FeCrAl CATCO potential to improve physical properties and reduce emission.